Cover Feature: Towards DNA‐Encoded Micellar Chemistry: DNA‐Micelle Association and Environment Sensitivity of Catalysis (Chem. Eur. J. 39/2021). Issue 39 (15th June 2021) - Klika Škopić, Mateja; Gramse, Christian; Oliva, Rosario; Pospich, Sabrina; Neukirch, Laura; Manisegaran, Magiliny; Raunser, Stefan; Winter, Roland; Weberskirch, Ralf; Brunschweiger, Andreas
Abstract : The development of DNA‐compatible reactions is central to advance DNA‐encoded library technology. Amphiphilic block copolymer micelles functionalized with sulfonic acid moieties assemble in water to micelles and localize the catalyst in them. DNA‐aldehyde conjugates were reacted to target heterocycles by micelle‐promoted Povarov‐ and Biginelli‐reaction with minimal DNA damage. Strikingly, DNA‐conjugates accumulated effectively in the micellar compartments as a prerequisite for compound synthesis. More information can be found in the Full Paper by R. Weberskirch, A. Brunschweiger, et al. (DOI: 10.1002/chem.202100980 ).